Am I pretty when I fly? an album of upside down drawings - Baez, Joan 1941- (Godine, 2023)
"Since retiring from active performing, Baez has focused her formidable talents on painting and drawing. This collection of drawings shows another side of Baez: lovingly loose and charming sketches on reoccurring themes such as politics, relationships, women, animals, and family. Each section, organized thematically, includes an introductory piece by the artist. Baez approaches her line drawings as exercises in freedom: she begins drawing upside down--often using her non-dominant hand--without any preconceived notion of where the lines might lead her"--Book jacket flap
Keywords: Baez, Joan -- 1941-; Zeichnung; Baez, Joan / https://isni.org/isni/0000000114552947; Baez, Joan / Notebooks, sketchbooks, etc; Folk musicians / United States / Biography; Drawing / 20th century; Drawing / 21st century; Baez, Joan; Drawing; Folk musicians; United States; 1900-2099; Biographies; Notebooks, sketchbooks, etc; Sketchbooks; Bildband